A short history of anti-rheumatic therapy. II. Aspirin - P. Marson; G. Pasero (Reumatismo, 2011)
The discovery of aspirin, an antipyretic, anti-inflammatory and analgesic drug, undoubtedly represents a milestone in the history of medical therapy. Since ancient times the derivatives of willow (Salix alba) were used to treat a variety of fevers and pain syndromes, although the first report dates back to 1763 when the English Reverend Edward Stone described the effect of an extract of the bark willow in treating malaria. In the XIX century many apothecaries and chemists, including the Italian Raffaele Piria and Cesare Bertagnini, developed the biological processes of extraction and chemical synthesis of salicylates, and then analyzed their therapeutic properties and pharmacokinetic and pharmacodynamic characteristics. In 1899 the Bayer Company, where Felix Hoffmann, Heinrich Dreser and Arthur Eichengrün worked, recorded acetyl-salicylic acid under the name “Aspirin”. In the XX century, besides the definition of the correct applications of aspirin in the anti-rheumatic therapy being defined, Lawrence L. Crawen identified the property of this drug as an anti-platelet agent, thus opening the way for more widespread uses in cardiovascular diseases.